An examination of evaluation users' preferences for program- and actor-oriented theories of change. (April 2017) - Ofek, Yuval
As programs and policies have grown in complexity, theory of change evaluation approaches and methods have become increasingly popular. While the academic literature often adheres to program-oriented theories of change, it is gradually being exposed to actor-oriented theories of change, which aim to enhance the flexibility of evaluations in order to adapt to growing complexity. Aside from the methodological considerations of when to use which approach, it is generally accepted that to increase their influence, evaluation approaches and methods should be suited both to the evaluated program and the preferences of intended users. But do we really know what approaches intended users prefer? Using a simulation-based survey and interviews with 148 public-sector employees in Israel, this article aims to provide an initial answer to this question. The results suggest that there is room to reconsider current perceptions of what intended users think. The findings have implications for the types of theories of change evaluators can suggest to intended users, with the ultimate goal of increasing the influence of evaluations.